Development and validation of a military integrity attitude scale - Yen, Chih-Long (Crime, law and social change, 2021)
Few empirical studies have investigated the issue of integrity in the military. This may be due, in part, to the lack of good measurement instruments. This study addressed this problem by developing a military integrity attitude scale (MIAS). Three studies were conducted to develop and validate the MIAS. A large sample size (N = 2375) was used in an exploratory and confirmatory factor analysis, and the results revealed the stable and good fit of the factor structure, while also demonstrating the scale’s good internal consistency, content validity, criterion-related validity, and discriminant validity. In addition, the MIAS was also shown to be able to effectively distinguish anti-corruption personnel and soldiers in the military; hence, it has good contrast group validity. The implications for future research are also discussed.